2020
DOI: 10.1101/2020.05.31.126128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurofunctional basis underlying audiovisual integration of print and speech sound in Chinese children

Abstract: 31Efficient integration of grapheme and phoneme is crucial for reading development 32 in alphabetic languages, and superior temporal cortex (STC) has been demonstrated 33 to be the most critical region for this process. To determine whether a similar 34 neural mechanism underlies such processing in non-alphabetic languages, and to 35 explore its relationship with reading, we conducted a functional magnetic resonance 36 imaging study in typically developing Chinese children. Highly frequent 37 pictographic char… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 88 publications
(222 reference statements)
0
13
0
Order By: Relevance
“…One interesting point should be noted that spatially very close but not overlapping clusters were found in the rSTG across any pairs of writing systems (Chi-W ⋂ Eng-W, rSTG, [60, −20, −10]; Chi-W ⋂ Pin, rSTG, [70, −16, −8]; Pin ⋂ Eng-W, rSTG, [66, −26, −6]). Previous studies demonstrated that the bilateral STG was involved in visual-audio integration both in English and Chinese reading (Holloway, van Atteveldt, Blomert, & Ansari, 2015; Kast, Bezzola, Jancke, & Meyer, 2011; McNorgan, Randazzo-Wagner, & Booth, 2013; Xia, 2020). Subtle anatomical separations supporting similar functions suggested that discrepant visual-audio linguistic features were integrated in subregions of the rSTG and supported the accommodation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting point should be noted that spatially very close but not overlapping clusters were found in the rSTG across any pairs of writing systems (Chi-W ⋂ Eng-W, rSTG, [60, −20, −10]; Chi-W ⋂ Pin, rSTG, [70, −16, −8]; Pin ⋂ Eng-W, rSTG, [66, −26, −6]). Previous studies demonstrated that the bilateral STG was involved in visual-audio integration both in English and Chinese reading (Holloway, van Atteveldt, Blomert, & Ansari, 2015; Kast, Bezzola, Jancke, & Meyer, 2011; McNorgan, Randazzo-Wagner, & Booth, 2013; Xia, 2020). Subtle anatomical separations supporting similar functions suggested that discrepant visual-audio linguistic features were integrated in subregions of the rSTG and supported the accommodation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a passive audiovisual paradigm that has been widely used in the previous fMRI studies investigating the neural basis of letter-sound integration (Figure 1). The details about the stimuli and procedure can be found in Xia et al (2020). In brief, 56 pictographic characters with high-frequency (M ± SD = 929 ± 1486 per million; Chinese Single-Character Word Database; https://blclab.org/pyscholinguistic-norms-database/; Liu et al, 2007) and are frequently used as radicals in phonograms were selected.…”
Section: Experimental Designmentioning
confidence: 99%
“…Both group comparison and individual differences analytic approaches were performed. Based on the prior research in typically developing children (Xia et al, 2020), we predicted that Chinese children with dyslexia would show a reduced audiovisual integration effect. In addition, dyslexic children may also display atypical brain-behavior correlations or recruit other brain regions to integrate cross-modal information.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations